The collection of the gracious service and borrowing of 1589 in the Audiencia de Charcas: institutional actors, political diligences and persuasive rhetoric, 1590-1593 - Castro-Flores, Nelson; De Nardi, Loris (Revista Complutense de Historia de América, 2025)
Contemporary research has focused on the donations or services provided free of charge that enabled the Crown to generate extraordinary revenue in Spanish America from the 16th century onwards. This was facilitated by the absence in Spanish America of a Cortes, which would have forced negotiations and delayed this tax collection. However, donations were also based on shared social representations of the loyal vassal who had to demonstrate his love for the monarch and repay his protection, particularly in his defence of the Catholic faith, as well as on conceptions of donation. Based on published and unpublished sources from Spanish and Bolivian archives, this article analyses the collection of the gracioso service tax in 1589 in the Audiencia de Charcas —which continued until the early 17th century— examining the participation of institutional actors, political proceedings and persuasive rhetoric aimed at sensitising and persuading Spanish and indigenous subjects to commit to the gracious service and borrowing contributions.